1973
DOI: 10.1113/jphysiol.1973.sp010186
|View full text |Cite
|
Sign up to set email alerts
|

Spinal interneurones involved in presynaptic controls of supraspinal origin†

Abstract: SUMMARY1. Interneurones presenting heterotopic and heterosensory convergence have been identified in laminae VI-VII of the lumbar dorsal horn in the cat. Stimulation of the hind limbs sometimes induced a bimodal response, but we considered only the late convergent discharge.2. The fact that response latencies are longer to hind limb than to forelimb stimulation at this level suggests the intervention of a supraspinal loop in the activation of spinal convergent units. This hypothesis is supported by the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This finding supports data from our previous studies that the latencies of HSP are variable in intact rats even during ketamine anaesthesia [2] and divided into two groups in conscious human subjects [5]. Previous studies in cats [26][27][28][29][30][31] demonstrated that primary afferent depolarization (PAD) could be evoked by stimulation of several CNS structures. These findings support the fourth mechanism proposed above that the principal nuclei involved in HSP production might be situated in the medulla but be influenced by other higher CNS structures.…”
Section: Discussionsupporting
confidence: 86%
“…This finding supports data from our previous studies that the latencies of HSP are variable in intact rats even during ketamine anaesthesia [2] and divided into two groups in conscious human subjects [5]. Previous studies in cats [26][27][28][29][30][31] demonstrated that primary afferent depolarization (PAD) could be evoked by stimulation of several CNS structures. These findings support the fourth mechanism proposed above that the principal nuclei involved in HSP production might be situated in the medulla but be influenced by other higher CNS structures.…”
Section: Discussionsupporting
confidence: 86%
“…The differences in the central latencies of the descending N and P waves from those of the segmental N1 and P2 waves are reminiscent of the animal studies (Besson and Rivot, 1973;Hongo et al, 1966;Menétrey et al, 1980;Skinner and Willis, 1970). Experiments with cats have shown that interneuronal populations are activated monosynaptically from different descending pathways.…”
Section: Origins Of Descending N and P Waves In Human Scpsmentioning
confidence: 94%
“…Thus, the interneurons producing the descending N wave may differ for the most part from those producing the segmental N1 wave, but some interneurons show convergence of the descending and segmental volleys (Besson and Rivot, 1973;Kostyuk and Vasilenko, 1979;Tobita et al, 2003). The degree of convergence of the descending and segmental volleys on the primary afferent terminals might be increased, since the descending P and segmental P2 waves interact more than the descending N and segmental N1 waves (Fig.…”
Section: Origins Of Descending N and P Waves In Human Scpsmentioning
confidence: 99%